THE HISTORY OF FIEP IN BOLIVIA (Fiep Bulletin - online, 2013)
Part of this document has been recorded by Edgar Zeballos Burgoa, Delegate General of FIEP (International Federation of Physical Education) Bolivia from 1992 to 2006. Unfortunately, in previous FIEP Bolivia administrations, few activities were carried out and the FIEP goals were not properly promoted in Bolivia. First Delegates. It is known that previous FIEP Delegates in Bolivia were Professor Emilio Sotomayor Ledezma (1974), Guido Ferrufino de La Paz and José Nuñez Ruiz de Cochabamba, and they have always wanted to integrate teachers with the teachers associations, but due to lack of economic resources and little interest from the teachers union, they never got to strengthen a homogeneous group, carrying out some training courses restricted to the regions and areas specifically oriented to physical education classes at school. A little bit of history. In 1987, the Higher Institute of Physical Activity (INSAF) was created in Santa Cruz de la Sierra, Bolivia, and within the expansion policies of this leading institution a delegation of teachers and students was called to participate in the 3rd International Congress of Physical Education and Sports of Foz do Iguaçu, 1988. On that occasion, we met the FIEP authorities John Andrews, Jorge Diaz Otañez and the coordinator in charge of the Congress in Iguaçu, Prof. Almir Gruhn. This contact was very important for the changes that would occur in FIEP Bolivia from that singular event on.